Searching for a Nuclear Settlement. European Union Nuclear Settlement With Iran - Fiedler, Radosław (Przegląd Strategiczny, 2016)
In the article is analyzed European Union crisis diplomacy with Iran, which finally brought to the final settlements. Beside the nuclear issues, in EU and Iran relations are visible other issues, as such as: human rights, security, energy and trade. In the 90’s and 2000’s EU proposed the formula critical and comprehensive dialogue. Now after nuclear settlement, crisis diplomacy with Iran is essential, due to the problems and challenges related with internal Iranian politics and its regional policy.